A preliminary study on the influence of high heel footwear on lumbar spine proprioception - Ganesh Balthillaya M; Prabhu Anupama; Bhatia Ridhima; Rao Lavanya; Bhat Triveni; Raja Prabu (Sciendo, 2020)
Study aim: High heel footwear (HHF) alters posture and kinetics of the lower limbs and spine. Various musculoskeletal disorders in the lower quadrant can occur as a consequence of HHF use. This study aimed to investigate the effect of habitual use of HHF on lumbar spine proprioception.